The Environmental Impacts of Omnivorous, Vegetarian, and Vegan Children and Adolescents in Germany: Results of the VeChi Diet and VeChi Youth Studies - Laureen Kuhl; Vanessa Keller; Stine Weder; Ute Alexy; Morwenna Fischer; Markus Keller; Andreas Michalsen; Alfred Längler; Andreas Sputtek; Wencke Gwozdz (Proceedings)
Background and objectives: There is a lack of data on the environmental impact of children’s and adolescents’ food consumption as most studies only consider adult dietary intake and, in addition, use hypothetical diets or focus on specific food products. Hence, our aim was to assess two indicators of environmental impact of the total diet among omnivorous (OM), vegetarian (VG), and vegan (VN) children and adolescents from Germany. Methods: Greenhouse gas emissions (GHGE) and land use (LU) were calculated using 3-day weighed dietary records from 820 participants (1–18 years old) of the cross-sectional VeChi Diet Study (n = 430, 1–3 years of age, conducted 2016–2018), the VeChi Youth Study (n = 390, 6–18 years, 2017–2019), and the life cycle-analyses food-item (SHARP-Indicators) database. Group differences of indicators were analysed using analysis of covariance. Results: On average, food consumption of OM, VG, and VN diets caused GHGE of 2.6, 1.6, and 1.0 kg CO2eq/kg food and LU of 3.1, 2.0, and 1.6 m2·year/kg food, respectively. The median total daily GHGE and LU amounts differed significantly between diet groups (p < 0.001). Standardisation to energy intake per 1000 kcal (GHGE: (OM) 2.2, (VG) 1.3, (VN) 0.9 kg CO2eq/1000 kcal; LU: (OM) 2.5, (VG) 1.6, (VN) 1.3 m2·year/1000 kcal) confirmed these results. Discussion and conclusions: To the best of our knowledge, this is the first evaluation to show that even in children and adolescents, the GHGE and LU caused by an OM diet is considerably higher than the GHGE and LU on a VG or VN diet. In this way, plant-based diets performed better in terms of environmental sustainability.